LEGAL MODEL OF ERADICATING ILLEGAL CIGARETTES AS A MEANS OF INCREASING STATE REVENUE - Bagyo Mulyono; Heri Hartanto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the legal framework and enforcement efforts to combat the circulation of illegal cigarettes in Indonesia, with a focus on the “Gempur Rokok Ilegal” program implemented by the Directorate General of Customs and Excise (DGCE) in the jurisdiction of KPPBC TMP B Surakarta. Using a doctrinal legal research method with statute and conceptual approaches, the research analyzes preventive and repressive enforcement measures against violations in tobacco excise. Findings show that despite extensive campaigns and enforcement, the distribution of illegal cigarettes remains high, influenced by economic incentives, weak deterrence, and geographic proximity to major tobacco-producing regions. The study concludes that optimal law enforcement requires more intensive surveillance, stronger community involvement, and stricter penalties to deter offenders, thereby safeguarding state revenue from tobacco excise.